Psycometric characteristics of the effort reward – imbalance questionnaire in professors sample from Lima - Loli Pineda, Alejandro Erasmo (2023)
The pandemic COVID19 implied drastic changes in the world, including educational institutions. According to the Comisión Económica para América Latina (CEPAL), 32 countries closed schools disturbing the life of more than 165 millions students and, of course professors also. To find out how educators felt during the pandemic period, several questionnaires can be used: Effort-Rewards Imbalance, Engagement, Burnout syndrome and Perceived Physical and Mental Health. However, before reaching this knowledge, it was necessary to determine the construct and differential validity of instruments in a sample of 353 Peruvian teachers. The results indicate that the mentioned tests have construct validity, as well as the differential one validity.